Anilogic animated logic: a good experience. - Huberto Noriega Noriega; Darwin Peña Gonzalez; Augusto Ospino Martinez (Universidad del Magdalena, 2014)
Below are several work experiences carried out at the University of Magdalena with students of the School of General Studies conducted by teachers Hubert Noriega Noriega, Ospino Augusto Dacier Darwin Pena Martinez and Gonzalez are summarized. The idea is to use new methodologies quo enrich learning and evaluation only, in particular laws of inference.